2006
DOI: 10.1111/j.1468-0432.2006.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Men's Entry into Female‐Concentrated Occupations: Issues of Masculinity and Social Class

Abstract: This article seeks to add to an understanding of why some men enter female-concentrated occupations (and why the majority do not). Drawing on the results of in-depth interviews with 27 men in a range of occupations, I illustrate and interpret the complex and often contradictory ways in which men approach the notion of working in female-concentrated occupations and examine the impact that this has on their occupational outcomes. The data suggest that different attitudes to female-concentrated work cannot in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
4
23

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(206 citation statements)
references
References 53 publications
(82 reference statements)
7
172
4
23
Order By: Relevance
“…Ray may have conceptualized work as a means of gender expression (David & Brannon, 1976;Monaghan, 2002) or affirmation; the lack of male colleagues may have served as evidence that he was violating gender norms, which may have generated or increased gender role strain (Pleck, 1981) and resulted in emotional distance from his work and diminished desire to excel. Similarly, Lupton (2006) found that men working in nontraditional occupations expressed concern with maintaining their sense of masculinity. Although Neil may have also believed that gender expression was a function of his work, his focus was on using work to express alternate gender expressions.…”
Section: Endorsement Of Masculinity Norms In the Nontraditional Work mentioning
confidence: 99%
“…Ray may have conceptualized work as a means of gender expression (David & Brannon, 1976;Monaghan, 2002) or affirmation; the lack of male colleagues may have served as evidence that he was violating gender norms, which may have generated or increased gender role strain (Pleck, 1981) and resulted in emotional distance from his work and diminished desire to excel. Similarly, Lupton (2006) found that men working in nontraditional occupations expressed concern with maintaining their sense of masculinity. Although Neil may have also believed that gender expression was a function of his work, his focus was on using work to express alternate gender expressions.…”
Section: Endorsement Of Masculinity Norms In the Nontraditional Work mentioning
confidence: 99%
“…To investigate men's gendered identity work in feminized occupations, and in keeping with a body of work that explores the marginal roles and identities of men in non-traditional work contexts (Lupton 2000(Lupton , 2006Heikes 1992;Author, 2004; Williams 1993), we concern ourselves with how 'being Other' is managed by the practices of doing masculinity. This contrasts with research that has concentrated on male dominance as a source of privilege and power (Collinson & Hearn 1994;Connell 1995;Kerfoot & Knights 1993, 1998 while at the same time disrupts the common reading of women as Other.…”
Section: Introductionmentioning
confidence: 99%
“…This gender stereotype of men as sexual aggressors is reported in other studies (Evans, 2002;Harding, 2008;O'Lynn, 2007 issue of masculinity and gender. This alternative approach has been adopted by Lupton (2006) in explaining men's entry into female-concentrated occupations in the UK.…”
mentioning
confidence: 99%